NVP-BSK805, an Inhibitor of JAK2 Kinase, Significantly Enhances the Radiosensitivity of Esophageal Squamous Cell Carcinoma in vitro and in vivo - Hua Y; Wang W; Zheng X; Yang L; Wu H; Hu Z; Li Y; Yue J; Jiang Z; Zhang X; Hou Q; Wu S (Dove Medical Press, 2020)
Yuhui Hua,1 Weijia Wang,1 Xiaoli Zheng,2 Ling Yang,2 Hongjin Wu,2 Zhaoyang Hu,2 Ying Li,2 Jing Yue,2 Zhenzhen Jiang,2 Xiaoyan Zhang,2 Qiang Hou,2 Shixiu Wu3 1Department of Pharmacy, Hangzhou Cancer Hospital, Hangzhou 310002, People’s Republic of China; 2Hangzhou Cancer Institution, Hangzhou Cancer Hospital, Hangzhou 310002, People’s Republic of China; 3National Cancer Center/National Clinical Research Center for Cancer/Cancer Hospital & Shenzhen Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Shenzhen 518116, People’s Republic of ChinaCorrespondence: Shixiu WuNational Cancer Center/National Clinical Research Center for Cancer/Cancer Hospital & Shenzhen Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, No. 113 Baohe Street Longgang District, Shenzhen, People’s Republic of ChinaEmail wushixiu@medmail.com.cnPurpose: Radiotherapy is one major curative treatment modality for esophageal squamous cell carcinoma (ESCC) patients. This study aimed to find out small-molecular kinase inhibitors, which can significantly enhance the radiosensitivity of ESCC in vitro and in vivo.Materials and Methods: Ninety-three kinase inhibitors were tested for their radiosensitizing effect in ESCC cells through high-content screening. The radiosensitizing effect of kinase inhibitors was investigated in vitro by detection of DNA double-strand breaks (DSBs) and clonogenic survival assay. By the establishment of xenograft tumor models in BALB/c nude mice, the radiosensitizing effect of kinase inhibitors was investigated in vivo.Results: Among the 93 kinase inhibitors tested, we found NVP-BSK805, an inhibitor of JAK2 kinase, significantly radiosensitized ESCC cells through enhancing DSBs, inhibiting DNA damage repair and arresting cell cycle in G2/M or G0/G1 phase. After treatment with NVP-BSK805, ESCC cells showed decreased clonogenic survival and delayed tumor growth in vivo. JAK2 kinase was highly expressed in tumor tissues of ESCC patients, while rarely expressed in matched normal esophageal epithelial tissues. Survival analysis revealed JAK2 kinase as a prognostic factor of ESCC patients treated with chemoradiotherapy.Conclusion: Our study discovered JAK2 kinase as an attractive target to enhance the radiosensitivity of ESCC cells in vitro and in vivo.Keywords: ESCC, radioresistance, JAK2, NVP-BSK805, DNA damage repair